A comprehensive assessment of turbulence at a tidal-stream energy site influenced by wind-generated ocean waves. (15th January 2020) - Thiébaut, Maxime; Filipot, Jean-François; Maisondieu, Christophe; Damblans, Guillaume; Duarte, Rui; Droniou, Eloi; Chaplain, Nicolas; Guillou, Sylvain
Abstract: Velocity measurements collected by an upward-looking acoustic Doppler current profiler were used to provide the first study of ambient turbulence in Alderney Race. Turbulence metrics were estimated at mid-depth during peak flooding and ebbing tidal conditions. The dissipation rate ε and the integral lengthscale ( L ) were estimated using two independent methods: the spectral method and the structure function method. The spectral method provided ε and ( L ) estimates with standard deviations twice lower than that obtained from the structure function method. Removal of wave and Doppler noise-induced bias when estimating the dissipation rate was shown to be a crucial step in turbulence characterization. It allowed for a significant refining in ( L ) estimates derived from the spectral and structure function methods of 35 % and 20 % respectively. The integral lengthscale was found to be 2–3 times the local water depth. It is considered that these findings could be valuable for current turbine designers, helping them optimizing their designs as well as improving loading prediction through the lifetime of the machines. Highlights: The first study of ambient turbulence in Alderney Race is provided. Two independent methods are used to quantify turbulence metrics. Removal of wave and Doppler noise-induced bias is a crucial step. The integral lengthscale was found to be 2–3 times the local water depth. Unique dataset of turbulence metrics computed at mid-depth are provided.